Polydopamine Nanoparticles Prepared Using Redox-Active Transition Metals - Salomäki M.; Ouvinen T.; Marttila L.; Kivelä H.; Leiro J.; Mäkilä E.; Lukkari J. (AMER CHEMICAL SOC, 2022)
Autoxidation of dopamine to polydopamine by dissolved oxygen is a slow process that requires highly alkaline conditions. Polydopamine can be formed rapidly also in mildly acidic and neutral solutions by using redox-active transition-metal ions. We present a comparative study of polydopamine nanoparticles formed by autoxidation and aerobic or anaerobic oxidation in the presence of Ce(IV), Fe(III), Cu(II), and Mn(VII). The UV-vis spectra of the purified nanoparticles are similar, and dopaminechrome is an early intermediate species. At low pH, Cu(II) requires the presence of oxygen and chloride ions to produce polydopamine at a reasonable rate. The changes in dispersibility and surface charge take place at around pH 4, which indicates the presence of ionizable groups, especially carboxylic acids, on their surface. X-ray photoelectron spectroscopy shows the presence of three different classes of carbons, and the carbonyl/carboxylate carbons amount to 5-15 atom %. The N 1s spectra show the presence of protonated free amino groups, suggesting that these groups may interact with the pi-electrons of the intact aromatic dihydroxyindole moieties, especially in the metal-induced samples. The autoxidized and Mn(VII)-induced samples do not contain metals, but the metal content is 1-2 atom % in samples prepared with Ce(IV) or Cu(II), and ca. 20 atom % in polydopamine prepared in the presence of Fe(III). These differences in the metal content can be explained by the oxidation and complexation properties of the metals using the general model developed. In addition, the nitrogen content is lower in the metal-induced samples. All of the metal oxidants studied can be used to rapidly prepare polydopamine at room temperature, but the possible influence of the metal content and nitrogen loss should be taken into account.